CONVERGENCES VIA áº›Ù€ PREÙ€ gÙ€ OPEN SET - Jassam, Ahmed A.; Esmaeel, R. B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The main aim of this paper is to use the notion  which was introduced in [1], to offered new classes of separation axioms in ideal spaces. So, we offered new type of notions of convergence in ideal spaces via the set. Relations among several types of separation axioms that offered were explained.